Peacebuilding in a Disparate Federation: Nigeria’s Experience: Array - Adegbami, Adeleke (Acta Universitatis Danubius. Relationes Internationales, 2020)
Conflict is an unavoidable part of human society, while peace is unarguably the most treasured asset of man. Nigeria has continued to have its fair share of challenges to peace, as the country continues to encounter various shattering conflict situations. Given the above, the study analyses peacebuilding in a disparate federation like Nigeria. The sources of data for the study were secondary data and the author's observation. The study revealed that the pattern of emergency of Nigeria into nationhood, whereby the country was forcibly incorporated into a nation by the British imperialist habitually breed conflict. The study further identified issues such as – ethnicity, the control of natural resources; the creation of states/ local governments and the citing of their administrative headquarters as a threat to peace in Nigeria. Other issues include - land ownership, boundaries, and land demarcation disputes and land inheritance problems; religious intolerance; and youth unemployment/ restiveness. Furthermore, the study revealed stakeholders for peacebuilding to include - political actors; state actors; military/security actors; economic entrepreneurs/business actors; civil society/ Non-Governmental Organisations; international/regional organisations; the media; professional groups; religious groups; and traditional institutions. The study also found that the successive government in Nigeria has not been adequately engaged and catered for the needs of her youth populations. This has repeatedly threatened the nation's security as youth are readily available for recruitment into armed and insurgent groups. The study concluded that for national cohesion and integration, socio-economic, as well as political development peace must be maintained.